DETERMINATION OF THE SURFACE DENSITY OF POLARIZATION CHARGE OF THE MAGNETIC FLUID JET IN UNIFORM ELECTRIC FIELD - Yuriy Ivanovich Dikansky; Oleg Vasil’evich Borisenko; Marita Albertovna Bedzhanyan (Вестник Северо-Кавказского федерального университета, 2022)
The article is dedicated to an actual problem of the study of the behavior of the magnetic fluid jet in electrical and magnetic fields. A new method of calculation of value of density of the surface charge formed on the magnetic fluid jet surface is proposed; the hypothesis of surface charge formation mechanism is presented.